O uno primordial e o vir a ser: o poder, a alegria e a força da vida que irrompe da natureza - Ferreira, Regiani Cristina Jacinto (2016)
This dissertation is dedicated to the Nietzsche's philosophical thinking and aims to investigate the redemption of the One primordial, which means, the strategies of the relief to the pain and the contradiction, which are attached to the alleged human nature. The discussion in question initiates with the approach of the cosmological narratives, which reveals the upcoming of the Greek philosophy, started by the pre- Socratics, Heraclitus and especially, the to be essence. There is found a conception of world which embarks the eternal conflict of the generation as well as the destruction from the opposite forces. This reality, the One primordial, is a reality that is captured by the intuition and it has a vitality which is not always kept hidden. Nevertheless, one is not easily understood, even less by the Socratic optimism that claimed that the possibility of knowing is limited only to the science. In other words, only the theoretical activity may redeem the human creature from their existential condition: pain and contraction. The comprehension of the Nietzschean proposition demands the analyses on how the natural artistic principles are performed and appeared, either as phenomenal world such as the art or properly spoken, such as the tragedy; as this one is the art of full redemption. The tragedy, to Nietzsche, is the appearing mode and the sole expression which is fulfilled with vitality that embraces the changeability from the One primordial. As it is within the tragedy that occurs the double action of the natural artistic principles, as it may know, the Dionysian and the Apollonian. The essence of the tragedy will be known by the analyses of these artistic forces, when Nietzsche's criticism is presented up to the Modern Aesthetics and to the Romanticism, in particular. This conceptual effort will also highlight the rupture with Schopenhauer. Last but not least, the comprehension of the Nietzschean argument in favor of the Barbara Greek Art empathizes his criticism to the optimism related to the Socratic rationalism, whose triumph coincided with the ban of the Dionysian within the Art. The rupture of the unstable harmony from Dionysian and Apollonian over the alleged choice for the last one, produced as result the weakening of the impulse figure, which is Apolo his own. The Socratic- Platonic philosophy does not tolerate the tragic art, but instead, it postulates the pedagogical moralism and its search for a true and unchangeable knowledge, an illusion of the reason that tyrannizes the human creature. The Art, in turn, brings to life a free illusion of the moral order, this legacy from Nietzsche's philosophy interrupts the strength and the vitality of the reconquered and free world of the dualism.